EFEKTIVITAS SUMBER NITROGEN PADA PUPUK ORGANIK YANG BERBEDA SEBAGAI SUBSTITUSI UREA PADA NUTRIEN KULTUR Nannochloropsis sp. - Sinurat, Paulin; SINURAT, PAULIN BERNADET; Irawan, Henky; Putri, Dwi Septiani (Jurnal Intek Akuakultur, 2026)
Nitrogen is one of the nutrients needed Nannochloropsis sp., but there is no determination of fertilizer dosage based on fertilizer nitrogen source. This study aims to determine the provision of organic fertilizers capable of substituting urea in nutrient cultures Nannochloropsis sp. and effective used as a source of nitrogen for cell populations Nannochloropsis sp.. This research was conducted in April-May 2025 at the Batam Marine Aquaculture Center. This study used a complete randomized design (RAL) with 1 Control and 3 treatments, namely: control (50 mg/L Urea, Za, TSP, EDTA), treatment a (dung bats, Za, TSP, EDTA), treatment B (Quail Dung, ZA, TSP, EDTA), treatment C (Dung swallows, ZA, TSP, EDTA), each 3 replications. The observed parameters include daily density, population peak, doubling time, light intensity and water quality. Results showed for 7 days maintenance of cell density Nannochloropsis sp. the highest growth was found in h-5 maintenance with the highest growth in treatment B (quail droppings) is 23.193.055 cells/ml with the fastest doubling time is 36.3 hours and the lowest growth in control is 17.468.056 cells/ml with the longest doubling time is 52.3 hours. The peak population for control and all treatments is found on H-5 maintenance. The light intensity during the study ranged from 9.100 lux. This result shows that the fertilizer of bat droppings, quail droppings and bird droppings can be a substitution of urea and effective as a source of nitrogen in the nutrient culture Nannochloropsis sp. for cell populations Nannochloropsis sp..